Acute Compartment Syndrome of the right lower extremity following Autologous Blood transfusion: A Case report - Sabzi, Feridun; Heidari, Aghigh; Ghasemi, Fataneh; Ahmadi, Abbas (International Journal of Cardiovascular Practice, 2016)
Compartment syndrome (CS) is an extremely rare complication during cardiac surgery and rare case reports have been linked to coronary artery bypass surgery.We report one case of right lower extremity compartment syndrome (CS) following inadvertent blood transfusion through a catheter which was inserted into a vein in the related extremity. Forceful pushing of blood through a delicate vein led to rupture of the vein wall and subsequent extravasation of blood into the perivascular tissue as into an intra-compartment portion of the lower extremity.Late detection of this complication led to compartment syndrome. The patient underwent emergency fasciotomy and concomitant removal of intra compartment and subcutaneous blood and fluids. After fasciotomy, the normal color of skin and pulse were recovered.